The 2017 Hampton reader : selected essays from a working-class think tank - Jenkins, Colin (Critical constructions., 2019)
Through dozens of diverse and timely political essays and analyses, this book addresses the most pressing problems of our contemporary world. Instead of the tired, detached academic inquiry that permeates from institutions of higher education, these pages contain writings that have been produced by political organizers and revolutionaries throughout the course of their daily activity in social, economic, and political movements.The 2017 Hampton Reader includes the most popular essays from The Hampton Institute: A Working-Class Think Tank. The Hampton Institute is an intellectual and political organization that seeks to develop the working class into a self-conscious class-for-itself capable of fundamentally changing the nature of society. The essays herein are the products of a collective of organic intellectuals united by the task of clarifying our political moment, sparking a revival in working-class intellectualism, and pushing the revolutionary struggles of our day forward.